An Asian Patient with Myoclonus-Dystonia (DYT11) Responsive to Deep Brain Stimulation of the Globus Pallidus Internus - Akinori Uruha; Katsuo Kimura; Ryoichi Okiyama (Case Reports in Neurological Medicine, 2014)
We describe the case of a 42-year-old Japanese woman with childhood-onset myoclonus, dystonia, and psychiatric symptoms, including anxiety, phobia, and exaggerated startle response. The diagnosis was confirmed as myoclonus-dystonia (DYT11) by identifying a mutation in the gene encoding ε-sarcoglycan. Interestingly, while motor-related symptoms in DYT11 generally improve with alcohol ingestion, the patient’s symptoms were exacerbated by alcohol intake. Her severe and medically intractable symptoms were alleviated by bilateral deep brain stimulation of the globus pallidus internus, with myoclonus and dystonia scores showing 70% improvement after the surgery compared to presurgical scores. This is the first report of a genetically confirmed case of DYT11 in Japan. This paper together with other recent reports collectively demonstrates that DYT11 patients are distributed worldwide, including Asia. Thus, a diagnosis of DYT11 should be considered when clinicians encounter a patient with childhood-onset myoclonus and/or dystonia with psychiatric symptoms, regardless of ethnic background.